2021
DOI: 10.1111/ases.12961
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of robot‐assisted laparoscopic rectal cancer surgery associated with robot‐assisted radical prostatectomy

Abstract: Introduction: Robot-assisted laparoscopic surgery has been performed in various fields, especially in the pelvic cavity. However, little is known about the utility of robot-assisted laparoscopic rectal cancer surgery associated with robot-assisted radical prostatectomy (RARP). We herein report the clinical impact of robot-assisted laparoscopic rectal cancer surgery associated with RARP.Methods: We experienced five cases of robot-assisted laparoscopic rectal cancer surgery associated with RARP. One involved rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…7 We recently performed robotic APR with en bloc prostatectomy using a standard retropubic approach for rectal cancer invading the prostate. 4 Heah and Wong reported three cases of robot-assisted rectal cancer surgery with en bloc prostatectomy, and, as in our previous case, concluded that this procedure could be performed safely with acceptable surgical outcomes. 8 These results indicate that robot-assisted laparoscopic resection may be an acceptable treatment option for rectal cancer invading the prostate.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…7 We recently performed robotic APR with en bloc prostatectomy using a standard retropubic approach for rectal cancer invading the prostate. 4 Heah and Wong reported three cases of robot-assisted rectal cancer surgery with en bloc prostatectomy, and, as in our previous case, concluded that this procedure could be performed safely with acceptable surgical outcomes. 8 These results indicate that robot-assisted laparoscopic resection may be an acceptable treatment option for rectal cancer invading the prostate.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, this approach is also expected to reduce adhesions around the pubis. Actually, we had great difficulty in dissection due to the presence of strong adhesions around the pubis when we have performed robotic low anterior resection after RARP 4 . So, we believe that it is very important to prevent pelvic adhesions because the number of cases of reoperation after RARP is expected to increase with the aging of society.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Locally advanced or recurrent cervical cancer was dominant for indication for TPE in non-rectal pelvic malignancy, although all gynecological neoplasms (cervical, endometrial, vulvar, or ovarian carcinoma) and lower urinary tract neoplasms (bladder or prostate cancer) are also candidates for TPE as reported in previous literatures ( 15 , 16 ). Moreover, TPE is indicated in patients with both urological and colorectal cancer occurring at the same time ( 8 , 17 - 19 ). Indication for TPE depends on various factors, including previous treatments and presence of unresectable metastasis and invasion of the pelvic wall, sciatic nerve, or sacral nerve plexus.…”
Section: Current Status Of Robot-assisted Tpementioning
confidence: 99%